A prospective, randomized, double-blind, controlled trial on the efficacy of carbon dioxide insufflation in gastric endoscopic submucosal dissection - Maeda, Y.; Hirasawa, D.; Fujita, N.; Obana, T.; Sugawara, T.; Ohira, T.; Harada, Y.; Yamagata, T.; Suzuki, K.; Koike, Y.; Kusaka, J.; Tanaka, M.; Noda, Y. (Endoscopy, 2013)
Background and study aims: Carbon dioxide (CO2) insufflation is expected to be safe and effective in endoscopic submucosal dissection (ESD) as well as in other endoscopic procedures. The present study aimed to clarify the usefulness and safety of CO2 insufflation in gastric ESD.Patients and methods: A total of 102 consecutive patients were randomly assigned to CO2 insufflation (CO2 group, n = 54) or air insufflation (Air group, n = 48). Abdominal pain and distension were chronologically recorded on a 100-mm visual analog scale (VAS). The volume of residual gas in the digestive tract was measured by computed tomography performed immediately after ESD. Results: Abdominal pain on a 100-mm VAS in the CO2 vs. Air group was 4 vs. 3 immediately after ESD, 4 vs. 4 one hour after the procedure, 3 vs. 3 three hours after the procedure, and 1 vs. 4 the next morning, showing no difference between the groups. In addition, there was no difference in abdominal distension on the 100-mm VAS over the time course of the study. The volume of residual gas in the digestive tract in the CO2 group was significantly smaller than that in the Air group (643 mL vs. 1037 mL, P < 0.001). The dose of sedative drugs did not differ between the groups. Neither the incidences of complications nor clinical courses differed between the groups.Conclusions: Compared with air insufflation, CO2 insufflation during gastric ESD significantly reduced the volume of residual gas in the digestive tract but not the VAS score of abdominal pain and distension.